TEACHERS’ CONCEPTIONS AND USE OF ASSESSMENT IN STUDENT LEARNING - Azis, Astuti (Indonesian Journal of Applied Linguistics, 2012)
Abstract: Education and schooling involve not only materials to be taught or how they should be taught but also how the teaching and learning are assessed. Studying teachers’ conceptions is important, as it relates to beliefs which influence teaching practices, including assessment. This article reviews several studies on teachers’ conceptions and practices of assessment conducted in six different countries. The objective of the study is to presents teachers’ conceptions of the role of assessment in teaching and learning from different contexts. Data were obtained from a careful review of international articles on the study of teachers’ conception of assessment using inclusion and exclusion criteria. The result of the review reveals that assessment relates to learning improvement and support the use of various strategies and tools in assessing students. However, the six different countries in the review interpret improvement in different ways which is influenced by several factors. Implications and suggestions for further study are also provided. Keywords: assessment, conceptions, review, improvement, accountability